Distress Tolerance Treatment for Weight Concern in Smoking Cessation Among Women: The WE QUIT Pilot Study. (July 2017) - Bloom, Erika Litvin; Wing, Rena R.; Kahler, Christopher W.; Thompson, J. Kevin; Meltzer, Sari; Hecht, Jacki; Minami, Haruka; Price, Lawrence H.; Brown, Richard A.
Fear of gaining weight after quitting cigarette smoking is a major barrier to smoking cessation among women. Distress tolerance, which refers to one's ability and willingness to tolerate physical and emotional discomfort, predicts successful behavior change. Novel interventions rooted in Acceptance and Commitment Therapy (ACT) have emerged that aim to increase distress tolerance and engagement in values-oriented behavior. In this study, we developed a 9-week, group-based distress tolerance intervention for weight concern in smoking cessation among women (DT-W). Using an iterative process, we piloted DT-W with two small groups ( n = 4 and n = 7) of female weight-concerned smokers. Results indicated that we successfully established the feasibility and acceptability of DT-W, which was well-attended and well-received. Biochemically verified 7-day point-prevalence abstinence rates at post-intervention, 1, 3, and 6 months were 64%, 36%, 27%, and 27%, respectively. We are now evaluating DT-W in a randomized controlled trial.